Analisis Penerapan Metode Fluctuating Fund System Dalam Pengelolaan Kas Kecil (Petty Cash) Pada PT. Artha Utama Sejahtera - Farra Anjani Sukarman; A. Sudrajat (CV. ITTC INDONESIA, 2024)
Artha Utama Sejahtera as a service company engaged in consulting and training services in increasing professional human resources in the occupational safety and health (K3) sector, faces challenges in managing petty cash efficiently and accurately. This research aims to analyze the application of the Fluctuating Fund System method in petty cash management at PT. Artha Utama Sejahtera. The Fluctuating Fund System method is a petty cash management method that adjusts the amount of petty cash according to the company's daily needs, in contrast to the fixed method (imprest) which sets a fixed amount of petty cash throughout a certain period. This research uses a qualitative descriptive approach by collecting data through interviews, observation and documentation. Data analysis was carried out by evaluating the application of the Fluctuating Fund System method, identifying the advantages and disadvantages of this method. The research results show that the application of the Fluctuating Fund System method at PT. Artha Utama Sejahtera is able to increase the efficiency of petty cash management. This method provides greater flexibility in daily expenditure, so it can accommodate urgent needs without having to wait for petty cash to be refilled. Apart from that, this method also minimizes the risk of accumulating unused funds, so that existing funds can be utilized optimally. However, this research also found several obstacles in implementing the Fluctuating Fund System method, such as difficulties in recording daily transactions and the need for stricter supervision to avoid misuse of funds. Therefore, it is recommended to improve the recording and monitoring system so that this method can be implemented more effectively. Thus, the author concludes that the Fluctuating Fund System method has great potential to increase the efficiency of petty cash management at PT. Artha Utama Sejahtera, as long as it is supported by an adequate recording and monitoring system.